Synthesis of voltage−sensitive optical signals: Application to panoramic optical mapping - Bishop, M; Rodriguez, B; Eason, J; Whiteley, J; Trayanova, N; Gavaghan, D (2006)
Fluorescent photon scattering is known to distort optical recordings of cardiac transmembrane potentials; however, this process is not well quantified, hampering interpretation of experimental data. This study presents a novel model, which accurately synthesizes fluorescent recordings over the irregular geometry of the rabbit ventricles. Using the model, the study aims to provide quantification of fluorescent signal distortion for different optical characteristics of the preparation and of the surrounding